Peptidyl Arginine Deiminases and Neurodegenerative Diseases - Tu, R.; Grover, H.M.; Kotra, L.P. (Current Medicinal Chemistry, 2016)
Peptidyl arginine deiminases (PADs) are a small group of isozymes that convert Arg residues on the surface of proteins into citrulline residues, typically as a part of posttranslational processing. PADs are present in most of the tissues, and the isozyme distribution is tissue-specific. In the past 15 years, it is becoming apparent that PADs are either upregulated or their catalytic activity is enhanced in certain disease conditions, including neurological diseases. In particular, hypercitrullinated proteins and elevated PAD activities are discovered in neurodegenerative conditions such as multiple sclerosis, Alzheimer’s disease etc. This review article reviews the status of PAD enzymes as targets in neurodegenerative conditions, and briefly outlines the efforts in medicinal chemistry to identify PAD inhibitors for the treatment of various neurodegenerative conditions.
Keywords: neurodegenerative diseases